Evaluation of GVHD And oral mucositis in patients submitted to HSCT at the STMO-CHC of UFPR - Stresser, Fernanda Aparecida; Warnavin, Stephanie Von Stein Cubas; Mobile, Rafael Zancan; Schussel, Juliana Lucena (Journal of Oral Diagnosis, 2023)
Oral graft-versus-host disease (GVHD) and oral mucositis (OM) are important complications of hematopoietic stem cell transplantation (HSCT) that significantly impact the patient's quality of life. In this context, this study aimed to evaluate the profile of patients undergoing allogeneic HSCT, assessing oral GVHD and OM occurrence. Data from medical records of patients that underwent HSCT between 2019 and 2021 were collected. Patients over 18 years old, with diseases or conditions requiring HSCT, were included. A clinical examination was performed to evaluate the occurrence of GVHD and OM. A total of 47 patients undergoing HSCT were evaluated of which 34.04% developed GVHD, and of these 81.25% have had oral involvement. As for OM, it affected 82.97% of the patients, with grades 3 and 4 being more detected. The most frequent previous disease was acute myeloid leukemia, and most of these patients received a related type of transplant (84.61%), fully compatible (53.84%), with bone marrow as a source of stem cells (53.84%). Most patients received the myeloablative conditioning regimen (69.23%). Cyclosporine was the most immunosuppressive agent used for the GVHD prevention associated with methotrexate (76.92%). Oral GVHD and OM are frequent and debilitating oral complications of HSCT, which can compromise a patient's general health and overall survival. Early diagnosis is important for a quick start of treatment and to reduce the impact on the patient's prognosis.